Primary aorto-esophageal fistula: Great masquerader of esophageal variceal bleeding - Kokatnur, Laxmi (Indian J Crit Care Med, 2015)
Aorto-esophageal fistula is a rare cause of upper gastrointestinal bleeding. Thoracic aneurysm, the most common cause of this condition, will slowly increase over time and can erode the wall of the aorta creating a fistula and leading to torrential bleeding. High clinical suspicion is required for timely diagnosis as common investigations routinely done for gastrointestinal (GI) bleeding, including esophagogastroduodenoscopy, fails to detect most cases. The classical triad of midthoracic pain, herald bleeding and fatal hematemesis described in this condition is seen in only one-third of cases. Physician should be wary of this condition, especially in elderly patients with uncontrolled GI bleeding and who are also at risk of thoracic aneurysm. Computed tomography angiogram detects most cases and emergent endovascular repair with stents controls the initial bleeding. Later, both the aorta and the esophagus are repaired and reconstructed in staged procedures.